2017
DOI: 10.1590/s1517-707620170002.0181
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive characterization of epoxy matrix composites reinforced with Luffa lignocellulosic fibers

Abstract: Luffa Cylindrica is a tropical plant from the Cucurbitaceae family, whose fruit becomes very fibrous when fully ripened. The lignocellulosic sponges of Luffa can be suitable for use as reinforcement of epoxy matrix composites, because they have a morphology with spatial 3-D arrangement as well as are eco-friendly materials (biodegradable, and high available) and have economic advantages compared to composites reinforced with synthetic fibers derived from non-renewable sources. Surface modification of the Luffa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…WAXD measurements further showed that the physical character of the filters was largely unaffected by the cationization reaction, apart from minor swelling of C75 and C150 (Figure S2). However, a small change in the crystalline character and content of the cationized filters could be observed compared to pristine cellulose (Figure S3). All filters showed crystalline planes belonging to cellulose I, which are (101), (101̅), (002), and (040) at around 14.8, 16.5, 22.6–22.9, and 34.2°, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…WAXD measurements further showed that the physical character of the filters was largely unaffected by the cationization reaction, apart from minor swelling of C75 and C150 (Figure S2). However, a small change in the crystalline character and content of the cationized filters could be observed compared to pristine cellulose (Figure S3). All filters showed crystalline planes belonging to cellulose I, which are (101), (101̅), (002), and (040) at around 14.8, 16.5, 22.6–22.9, and 34.2°, respectively .…”
Section: Resultsmentioning
confidence: 99%
“…Observa-se que um dos picos mais acentuados é o de Platina, porém este pico refere-se a recobrimento da amostra. Além disso, é possível observar picos característicos a Silício e Cálcio, entretanto como citado por Quinayá [10], esses picos são devidos a alguns precipitados presentes na fibra. Na Figura 5 é mostrado o difratograma obtido para o compósito com os três teores analisados 10, 20 e 30% de reforço, onde é possível observar a presença de picos apresentam os picos referentes aos planos cristalinos característicos dos materiais lignocelulósicos e halos amorfos em aproximadamente 2θ = 25º que são característicos do compósito epoxídico [11,12].…”
Section: Resultsunclassified
“…The results showed that the elastic modulus values are higher in luffa/epoxy composites made from fibers treated with mercerization and hornification, in which this may be related to higher crystallization values of the treated fibers and efficient removal of non-cellulosic components from the amorphous regions [30]. A previous study emphasizes that the effect of the mercerization treatment by weight of NaOH on the fibers produces only a small increase in flexural strength, and the best results were obtained with the 5% NaOH solution [1].…”
Section: Mechanical Properties Of the Bushing As Reinforcement In A M...mentioning
confidence: 99%